IMPLIKASI PEMBERIAN KOMPENSASI TERHADAP DISIPLIN KERJA PEGAWAI (STUDI KASUS DI FAKULTAS EKONOMI DAN BISNIS UNSRAT) - Setiawan, Anggun; Saerang, Ivone; Kojo, Christoffel (Universitas Sam Ratulangi, 2017)
Â Top of FormThe main question in this study is whether the provision of compensation affect the discipline of work, especially on the study staff at the Faculty of Economics and Business UNSRAT. Based on the background and the formulation of the above problems, this study aims to determine and analyze the effect of compensation on the discipline of employee work studies at the Faculty of Economics and Business UNSRAT. Researchers took data using questionnaires on the civil servants of the study of Faculty of Economics and Business UNSRAT which amounted to 41 people. The research variable that the adoptive researcher is compensation and work discipline with primary data collected through questionnaire and using quantitative descriptive analysis technique. For simple linear regression test found value of constant equal to 7,686 which mean when giving of compensation (X) equal to zero hence work discipline (Y) equal to 7,686. Regression coefficient value found at 0.619 positive value so it can be concluded that the compensation has a positive effect on work discipline. The value of regression coefficient also shows if the variable implication of compensation increases 1 unit then the work discipline will rise by 0.619. The value of correlation coefficient of 0.624 menunujukkan there is a strong relationship between the two variables with the value of coefficient of determination of 0.389 which means the variable implications of compensation affect 38.9% of the discipline of work. The researcher then tested the hypothesis by looking at the value of T arithmetic and found 4.983 which is much higher than the value of T table for n 41 of 1.638 so it can be concluded that Ha accepted and H0 rejected or in other words the Implication of Compensation (X) Work Discipline (Y). Through the process of collecting data and testing with quantitative methods the researcher then concluded that the implication of compensation has a positive and significant effect to the work discipline on civil servant studies in the Faculty of Economics and Business UNSRAT.Bottom of FormKeyword : Implication, Compensation, Work Discipline, Civil Servant